Sustainable Management Practices - Sarfraz, Muddassar; Ibrahim Adbullah, Muhammad; Rauf, Abdul; Ghulam Meran Shah, Syed (IntechOpen, 2019)
This book encapsulates the advanced concept of sustainable management and will enlighten readers to understand this concept for practical applications. The book's salient features are as follows: • Illustrates the basic concepts of human psychology causing risk factors such as burnout; • Differentiates adaptive sustainable measures and management practices; • Emphasizes sustainable agriculture management to confront the current dynamic environment and defines specific rules for enterprise development while coping with global climate change; • Assesses inertia with respect to economic development; • Constructs the linkage between technological strategies and innovation among construction companies; • Demonstrates non-financial reporting through theoretical and empirical evidence; • Elucidates the principles of equality, elaborating the managing of equality and diversity in a Steiner school